Avaliação das características genéticas de abelhas africanizadas (Apis mellifera L.) importantes na seleção de rainhas matrizes para a produção de mel - Gomes, Renata Valéria Regis de Sousa (Universidade Federal Rural do Semi-Árido, 2016)
This work aimed to evaluate africanized bee (Apis mellifera L.) phenotypic characteristics, important in selecting matrix queens for honey production. Thirty africanized bee (Apis mellifera L.) colonies were transferred from partner beekeeping apiaries in coastal zone and South Zona da Mata of Pernambuco to experimental apiary of Animal Science Department (AEDZ/UFRPE). Colonies were fortnightly evaluated in the period from January 2014 to February 2016 and data of 89 queens of colonies or families were recorded. Energy and protein food was provided in off-season period. Infestation rate in colonies with Varroa destructor and infection degree with Nosema were verified, as well as hygienic behavior, queen egg laying, defensiveness and honey production tests were carried out in the first experimental phase and selection index (IS) was obtained of analyzed colonies. For the 2nd experimental phase, 1st, 2nd and 3rd generation queens were produced; daughters of matrixes with IS ≥ 8.0 and honey production was evaluated. Sixty-two out of 89 queens observed died naturally, presenting average longevity of 6.4 ± 2.9 months. Natural reproduction peak period is between September and December. The queen perform egg laying all months of the year, and as temperature increases and humidity and rainfall decrease, queen oviposition intensity is higher; thus brood comb increases. The diet used showed economic viability, avoided swarm loss and stimulated queen egg laying. Low level of Varroatose (2.92% ± 2.02%) and low intensity of Nosema infection were found. Success in queen cell production was 98% in acceptance of transferred larvae. Genetic gain was observed of 0.7 Kg in honey production at colonies with 3rd generation queens; which represents increasing of 5.4% of honey production, related to matrix colonies and 49.2% compared to production in partner beekeeping apiaries. These results are very encouraging, leading us to believe in breeding program success, using the variables and calculation format for selection index used in this work and give us subsides for possible adjustments in management of production apiaries, in accordance with environmental conditions of this region, aiming at professional beekeeping growth and increased honey production
Evaluation of genetic characteristics of africanized bees (Apis mellifera L.), important in selecting matrix queens for honey production
Keywords: Melhoramento; Índice de seleção; Apicultura; Comportamento higiênico; Produção de mel; Abelha africanizada; Apis mellifera L; Improvement; Selection index; Beekeeping; Hygienic behavior; Honey production; Africanized bee; Apis mellifera L; CIENCIAS AGRARIAS::MEDICINA VETERINARIA